Environmental issues and the importance of science education for the empowerment of indigenous people in the Amazon (Research, Society and Development, 2021)
This work aimed to understand how environmental problems can be worked on in Science education in indigenous schools, through a reflection of the indigenous themselves. Questionnaires were applied consisting of nine open-ended questions, involving data on environmental problems and Science teaching in indigenous schools. One hundred and twelve indigenous students in the formation of the Degree in Intercultural Education at the Federal University of Rondônia participated in the survey. The results indicate that the loss of the fores tis a striking fator in relation to environmental factors, involving burning, illegal timber extraction and deforestation. These factors are motivated by man’s ambition and greed. In relation to environmental problems, 84.8% believe that they can be worked on in the school curriculum, specifically in the subjects of science and biology (29.8%). The themes addressed in school refer to factors that affect the environment and when they were worked on involved different teaching strategies. It is considered that it is possible, through planning and the formation of new indigenous teachers, that these views on environmental problems can be reflected in the science curriculum of indigenous schools, becoming essential factors in the search for autonomy and affirmation of cultural identity.